A leverage-based model of speculative bubbles - Gadi Barlevy (Federal Reserve Bank of Chicago, 2008)
This paper develops an equilibrium model of speculative bubbles that can be used to explore the role of various policies in either giving rise to or eliminating the possibility of asset bubbles, e.g. restricting the use of certain types of loan contracts, imposing down- payment restrictions, and changing inter-bank rates. As in previous work by Allen and Gorton (1993) and Allen and Gale (2000), a bubble arises in the model because traders are assumed to purchase assets with borrowed funds. My model adds to this literature by allowing creditors and traders to enter into a more general class of contracts, as well as by allowing speculators to trade strategically.
Keywords: 330; Bubbles; Börsenkurs; Wertpapierspekulation; Theorie; USA